Temporal sex ratio, growth patterns and condition factor of the blue swimming crab (Portunus pelagicus) in Northern of Tiworo Strait waters, Southeast Sulawesi, Indonesia - Oce Astuti; Naslina Alimina; Safilu Safilu; Emiyarti Emiyarti; La Sara; Wa Nurgayah; Ani Rahmadani; Ira Skel (Aceh Journal of Animal Science, 2020)
Blue swimming crabs Portunus pelagicus occupied Tiworo Strait waters has been experiencing heavy pressure due to high exploitation and damaging its habitat caused by conversion to be a port or jetty particularly in the intertidal and subtidal zones closed to mangrove areas and river mouth. Those zones constitute main habitats of BSCs. The study aimed to analyze temporal sex ratio (SR), growth patterns and condition factor (CF) of BSCs in Tiworo Strait waters which was conducted in June–December 2018. The BSC samples were taken monthly using collapsible pot. Each sample taken was identified its sex, measured its CW and weighed its BW. Monthly SR of male and female was counted, while BW–CW relationship was analyzed using a simple linear regression. Growth patterns and CF were derived and analyzed from BW–CW regression. The results of study showed that monthly BSC SR of male and female showed females preponderated over males, except in November. The growth pattern of male and female was negative allometric (b 3). Data of BSCs CF were mostly influenced by growth coefficient (b), namely the higher b the lower CF. This condition is frequent happening in BSC population dominated by juvenile and mature stages. This study showed most BSCs found in this location were juvenile which indicated as their nursery ground in the intertidal zone dominated by sand substrate closed to mangrove forest.